Pragmatic Functions of Expressive Speech Acts in a Creative Interview: A Case Study of Taylor Swift and Martin McDonagh - Utami, Sovia Lutvianita; Yuliati, Yuliati (Dinasti Publisher, 2025)
This research aims to analyze the pragmatic functions of expressive speech acts in the creative interview between Taylor Swift and Martin McDonagh. The focus of this study is to identify the types of expressive speech acts that emerge and their role in building interpersonal relationships and creating an authentic communication atmosphere. This research employs a descriptive qualitative method with pragmatic discourse analysis techniques. Data was collected through video interview transcripts between the two figures, then analyzed based on Searle's speech act theory and Leech's politeness principle to identify the forms and functions of expressive speech acts used. The research results show that expressive speech acts such as expressions of gratitude, apologies, compliments, and sympathy are predominantly used in this interview. The use of these expressive speech acts functions to strengthen interpersonal relationships, build creative solidarity, and create a warm and personal conversational atmosphere. Furthermore, the egalitarian and creative interview context contributes to enriching the expressive dimension in the interaction, making the communication feel more authentic and meaningful for both speakers and the audience. These findings affirm the importance of expressive speech acts in building effective communication in the media and entertainment domain.